Doprowadzi wyrazenia do najprostszej postac i oblicz ich wartosc liczbowa dla podanych zmienych

a)(2a-3b-1)-(3a+2b-4)-(a-6b+2) dla a=-3 dla b=-5
b)-(3a-2b-3c)+(5a-4b+4c)-(a-5b-c) dla a=-6 dla b=3 dla c=-1
c)(2x²+3x-5)-(3x²-5x+8) dla x=3
d)-(2x-x²)-[2-3x-(2x²-3x-4)] dla x=-1/2
e)3x[-2-3x²)+(1-3x+x²)]+4 x² dla x=-0,3

3

Odpowiedzi

2010-01-05T00:12:11+01:00
A)(2a-3b-1)-(3a+2b-4)-(a-6b+2) dla a=-3 dla b=-5
(2a-3b-1)-(3a+2b-4)-(a-6b+2)
2a-3b-1-3a-2b+4-a+6b-2=-2a+b+1

-2a+b+1=-2*(-3)-5+1=6-5+1=2

b)-(3a-2b-3c)+(5a-4b+4c)-(a-5b-c) dla a=-6 dla b=3 dla c=-1
-(3a-2b-3c)+(5a-4b+4c)-(a-5b-c)=-3a+2b+3c+5a-4b+4c-a+5b+c=
=a+3b+8c

a+3b+8c=-6+3*3+8*(-1)=-6+9-8=-5

c)(2x²+3x-5)-(3x²-5x+8) dla x=3
(2x²+3x-5)-(3x²-5x+8)=2x²+3x-5-3x²+5x-8=-x²+8x-13

-x²+8x-13=-3²+8*(-3)-13=-9-24-13=-46

d)-(2x-x²)-[2-3x-(2x²-3x-4)] dla x=-1/2
-(2x-x²)-[2-3x-(2x²-3x-4)]=-2x+x²-2+3x+2x²-3x-4=3x²-2x-6

3x²-2x-6=3*(-½)²-2*(-½)-6=3*¼+1-6=¾-5=-4¼

e)3x[-2-3x²)+(1-3x+x²)]+4 x² dla x=-0,3
3x[-2-3x²)+(1-3x+x²)]+4 x²=3x[-2-3x²+1-3x+x²]+4 x²=
=3x[-2x²-3x-1]+4x²=-6x³-9x²-3x+4x²=-6x³-5x²-3x

-6x³-5x²-3x=-6*(-0,3)³-5*(-0,3)²-3*(-0,3)=
=-6*(-0,3)³-5*(-0,3)²-3*(-0,3)=6*0,027-5*0,09+0,9=0,162-0,45+0,9=
=0,612
1 5 1
2010-01-05T00:12:36+01:00
A) 2a -3a -a -3b -2b +6b -1 + 4 - 2 = -2a + b +1
6 - 5 + 1 = 2
b) -3a +2b +3c +5a -4b +4c -a + 5b +c = a + 3b +8c
-6 + 9 - 8 = -5
c) 2x² - 3x² +3x + 5x -5 -8 = -x² + 8x - 13
-9 + 24 - 13 = 2
d) -2x + 3x - 3x + x² +2x² - 2 - 4 = -2x +3x² - 6
1 + ¾ - 6 = 4,25
e) -6x - 9x³ + 3x -9x² + 3x³ + 4x² = -3x -5x² -6x³
0,9 - 0,45 + 0,162 = 0,612

Chyba dobrze...
Najlepsza Odpowiedź!
2010-01-05T01:11:44+01:00
A) (2a-3b-1)-(3a+2b-4)-(a-6b+2)= 2a-3b-1-3a-2b+4-a+6b-2= -2a+b+1= (-2)*(-3)+(-5)+1= 6-5+1=2
b) -(3a-2b-3c)+(5a-4b+4c)-(a-5b-c)= -3a+2b+3c+5a-4b+4c-a+5b+c= a+3b+8c= -6+3*3+8*(-1)= -6+9-8=-5
c) -(2x-x^2)-[2-3x-(3x^2-3x-4)]= -2x+x^2-(2-3x-3x^2+3x+4)= -2x+x^2-2+3x+3x^2-3x-4= 4x^2-2x-6= 4*3^2-2*3-6= 4*9-6-6=36-6-6= 24
d) -(2x-x^2)-[2-3x-(2x^2-3x-4)]= -2x+x^2-(2-3x-2x^2+3x+4)= -2x+x^2-2+6x+2x^2-3x-4= x^2+x-6= (-1/2)^2+(-1/2)-6= 1/4-1/2-6= 1/4-2/4-6= -1/4-6= -6 1/4
e) 3x-[-2-3x^2+(1-3x+x^2)]= 3x-(-2-3x^2+1-3x+x^2)=3x+2+3x^2-1+3x-x^2= 2x^2+6x+1= 2*(-0,3)^2+6*(-0,3)+1= 2*0,09-1,8+1=0,18-1,8+1=-0,62
4 4 4